2005
DOI: 10.1681/asn.2004090740
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury, Mortality, Length of Stay, and Costs in Hospitalized Patients

Abstract: The marginal effects of acute kidney injury on in-hospital mortality, length of stay (LOS), and costs have not been well described. A consecutive sample of 19,982 adults who were admitted to an urban academic medical center, including 9210 who had two or more serum creatinine (SCr) determinations, was evaluated. The presence and degree of acute kidney injury were assessed using absolute and relative increases from baseline to peak SCr concentration during hospitalization. Large increases in SCr concentration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

64
2,106
17
84

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,986 publications
(2,271 citation statements)
references
References 17 publications
64
2,106
17
84
Order By: Relevance
“…In a consecutive sample of 19 982 adults admitted to an urban medical center, Chertow et al 11 found that patients with an increase in SCr of just 0.3-0.4 mg per 100 ml had a 70% higher multivariable-adjusted odds of death than did patients with little or no change in SCr. Other investigators have reported similar findings in patients with congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a consecutive sample of 19 982 adults admitted to an urban medical center, Chertow et al 11 found that patients with an increase in SCr of just 0.3-0.4 mg per 100 ml had a 70% higher multivariable-adjusted odds of death than did patients with little or no change in SCr. Other investigators have reported similar findings in patients with congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Recently, several investigators have shown that small changes in kidney function in hospitalized patients are important and have an impact on outcome. [10][11][12] Subsequently, the terminology of ARF has been shifted to acute kidney injury (AKI). The Acute Kidney Injury Network (AKIN) criteria provide a uniform definition of AKI and are increasingly used in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical features include oliguria or anuria, elevation of serum creatinine and electrolyte disturbances (17) . The incidence of AKI may be associated with periods of prolonged hospitalization resulting in increased morbidity and mortality and, consequently, increase of hospital costs of these patients (18) .…”
Section: Implications For Practicementioning
confidence: 99%
“…In native kidneys, IRI is a common cause of acute kidney injury (AKI) in patients who are undergoing cardiac surgery or with critical illness, and it is associated with high mortality and morbidity (Levy et al, 1996;Schiffl et al, 2002;Chertow et al, 2005;Bellomo et al, 2008;Kellum et al, 2008;Kinsey et al, 2008). For decades, non-steroidal antiinflammatory drugs (NSAIDs) have been used successfully in the treatment of numerous clinical diseases for their anti-inflammatory and analgesic effects.…”
Section: Introductionmentioning
confidence: 99%